2001
DOI: 10.1029/2001jb000359
|View full text |Cite
|
Sign up to set email alerts
|

Fluvial incision and tectonic uplift across the Himalayas of central Nepal

Abstract: Abstract. The pattern of fluvial incision across the Himalayas of central Nepal is estimated from the distribution of Holocene and Pleistocene terraces and from the geometry of modem channels along major rivers draining across the range. The terraces provide good constraints on incision rates across the Himalayan frontal folds (Sub-Himalaya or Siwaliks Hills) where rivers are forced to cut down into rising anticlines and have abandoned numerous strath terraces. Farther north and upstream, in the Lesser Himalay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

55
692
4
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 713 publications
(754 citation statements)
references
References 76 publications
55
692
4
3
Order By: Relevance
“…Slingerland et al [1998] compared slope-area relationships predicted by the stream power and tools algorithms, under equilibrium conditions, with data from Taiwan and concluded that these data do not permit discrimination between the different models because sediment flux appeared to scale roughly as a power of drainage area. By comparing stream profiles in the frontal Himalayas to incision rates measured from abandoned fluvial terraces, Lavé and Avouac [2001] showed that the rate of incision in these rivers is better described by an excess stream power model than by a simple stream power law. Finally, DeYoung [2000] compared predictions from a linear stream power model and a linear undercapacity model to observed incision of streams on western Kauai (Hawaii) and concluded that the undercapacity model predicted the evolution of these profiles, in particular the sections downstream of major knickpoints, better than the linear stream power model.…”
Section: Fluvial Incision Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Slingerland et al [1998] compared slope-area relationships predicted by the stream power and tools algorithms, under equilibrium conditions, with data from Taiwan and concluded that these data do not permit discrimination between the different models because sediment flux appeared to scale roughly as a power of drainage area. By comparing stream profiles in the frontal Himalayas to incision rates measured from abandoned fluvial terraces, Lavé and Avouac [2001] showed that the rate of incision in these rivers is better described by an excess stream power model than by a simple stream power law. Finally, DeYoung [2000] compared predictions from a linear stream power model and a linear undercapacity model to observed incision of streams on western Kauai (Hawaii) and concluded that the undercapacity model predicted the evolution of these profiles, in particular the sections downstream of major knickpoints, better than the linear stream power model.…”
Section: Fluvial Incision Modelsmentioning
confidence: 99%
“…However, it is well known that incipient motion of bed load, which will do most abrasive work on the streambed, occurs only when a threshold shear stress is exceeded. Several fluvial incision algorithms [e.g., Densmore et al, 1998;Lavé and Avouac, 2001;Sklar and Dietrich, 1998;Tucker and Slingerland, 1997] therefore include such a threshold…”
Section: Fluvial Incision Modelsmentioning
confidence: 99%
“…Pazzaglia et al, 1998;Berryman et al, 2000;Avouac, 2000, 2001;Pazzaglia and Brandon, 2001;Brocard et al, 2003;Tomkin et al, 2003;Brocard and van der Beek, 2006). For example, Lavé and Avouac (2001) and Tomkin et al (2003) tested stream erosion models using data on spatial variations in channel incision rate in the central Nepal Himalayas, and the Olympic Mountains, northwestern USA, respectively. Similarly, Kirby and Whipple (2001) used known spatial variations in rock uplift and erosion rates in the Siwalik Hills to test the unit stream-power and linear shear-stress incision models.…”
Section: Natural Experiments In Landscape Evolution 1455mentioning
confidence: 99%
“…The Yarlung Tsangpo has four major knickpoints separating lower gradient reaches (Figure 7a). Notable bulging through its upper and central lengths has been attributed to repeated blockage by glaciation (Korup and Montgomery 2010), localized aridity (Sobel et al 2003) or local fault offset (Lavé and Avouac 2001). Potential erosion fluctuates along the longitudinal profile, varying in relation to slope.…”
Section: Resultsmentioning
confidence: 99%